2019
DOI: 10.1029/2019gb006326
|View full text |Cite
|
Sign up to set email alerts
|

Iron Distribution in the Subtropical North Atlantic: The Pivotal Role of Colloidal Iron

Abstract: Key Points Size‐fractionation reveals that colloidal iron is more important than soluble iron for distribution of dissolved iron in North Atlantic Colloidal iron is the predominantly active species at key supply and removal processes of the dissolved iron cycle Global comparison suggests that the colloidal iron fraction in mesopelagic zone is determined by the local lithogenic contribution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 77 publications
(151 reference statements)
5
43
0
Order By: Relevance
“…First, dAl in the upper 100 m displays a strong concentration gradient with values increasing westward from 13 to 49 nmol/kg between 31° and 58°W. This concentration gradient correlates well with that of the dissolved iron from the same study (Kunde et al., 2019). Second, a marked dAl minimum (<15 nmol/kg) was observed across the entire GApr08 zonal section between 700 and 1,500 m depth.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…First, dAl in the upper 100 m displays a strong concentration gradient with values increasing westward from 13 to 49 nmol/kg between 31° and 58°W. This concentration gradient correlates well with that of the dissolved iron from the same study (Kunde et al., 2019). Second, a marked dAl minimum (<15 nmol/kg) was observed across the entire GApr08 zonal section between 700 and 1,500 m depth.…”
Section: Resultssupporting
confidence: 68%
“…This would suggest that up to 50% of the measured dAl concentration at Snakepit can be attributed to the hydrothermal vent. Note that a dissolved iron concentration maximum at 3,300 m at station 4 has also been attributed to hydrothermal venting (Kunde et al., 2019). Hydrothermally derived dAl has been previously reported for the MAR (up to 53 nmol/kg at the TAG vent site, Lunel et al., 1990; Measures et al., 2015).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…3). Colloidal species of trace metals appear more important than soluble species in supply and removal processes in oceanic and coastal systems (97), and this will almost certainly depend on the mineralogy of the colloid/nanoparticles usually included in the filterable fraction (41).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen fixation is not the only way that Trichodesmium can acquire fixed N (Dyhrman et al, 2006;Küpper et al, 2008;Mills et al, 2004;Sañudo-Wilhelmy et al, 2001). In culture, Trichodesmium can be grown on multiple nitrogen sources including urea; in fact, it has been reported that nitrogen fixation provides less than 20 % of the fixed N demand of cells, and a revised nitrogen fixation model suggests that Trichodesmium takes up fixed N in the field (McGillicuddy, 2014;Mulholland and Capone, 1999).…”
Section: The Intersection Of Fe P and N Stressmentioning
confidence: 99%